O ATO COATOR COMO NORMA JURÍDICA - Bertuloso, Leonardo Duarte (2020)
Everything in the world exists because it is externalized through language. The human being uses language not to describe the world, but to create it. In naming things and externalizing that nomination, man does not describe them, but creates them. Thus,